PENGARUH MENEJEMEN RISIKO, TINGKAT KEUNTUNGAN, DAN PEMAHAMAN KONTRAK TERHADAP AGENCY PROBLEM - Eeng Juli Efrianto (JURNAL AGHNIYA, 2019)
Abstract Agency problems are always inherent in parthership products, not least in musyarakah contracts which incidentally are products with sharia compliance implementation. This research aims to examine management factors, the level of profit and risk, and understanding of the contract towards the possibility of agency problems in the musyarakah contract. This is a field research with 50 respondents obtained by random sampling method. The results of this study are that the contract understanding variable does not affect the emergence of agency problems, variable level of profit and level of risk have a positive effect on the likelihood of agency problems, management variable does not affect the agency problem, and together the contract understanding variable, the level of profit and risk, and the management have a significant effect on the occurrence of the agency problem. Keyword: agency problem, Musyarakah contract, management, the level of profit and risk, understanding of contract